Effect of milling intensity on the properties of chitin, chitosan and chitosan films obtained from grasshopper - Zhu, Hongguang; Tang, Hanqi; Li, Fei; Sun, Haixin; Tong, Litao (International journal of biological macromolecules, 2023)
To obtain high-quality insect products, milling was used as a modification tool and its effect on grasshopper chitin, chitosan and chitosan films was investigated. Three grasshopper powders were obtained and classified into coarse-milled powder (CMP, D90 = 956 μm), medium-milled powder (MMP, D90 = 492 μm), and ultrafine-milled powder (UMP, D90 = 79.1 μm). Fourier transform infrared spectroscopy illustrated that no drastic change due to milling was observed, but the crystallinity (X-ray diffraction) and thermal stability (Thermogravimetric analysis) of the chitin, chitosan and chitosan films reduced with increasing milling intensity. Besides, the purity of the chitin and the yield of chitosan obtained from UMP were improved. Chitosan prepared from UMP was also characterized by high degree of deacetylation (65.6 %) and solubility and rather low molecular weight (11.5 kDa), viscosity and water/fat binding capacity. The finer the powder used as the extraction material, the thinner the chitosan films and the more compact the structure. On the whole, the chitosan films prepared from the MMP had higher mechanical properties and better moisture-keeping ability on strawberries compared with CMP and UMP films. This study establishes the role milling intensity played in the modification of grasshopper products and provides a reference for practical applications. •Ultrafine milling process helps to improve the purity of the resulting chitin.•Higher deacetylation and solubility of chitosan prepared from fine powder.•Intense milling reduces the molecular weight and crystallinity of insect products.•The finer the powder, the thinner but more compact the structure of chitosan film.•Chitosan film prepared by moderate milling has the best fruit preservation effect.